Improvement in running economy after 6 weeks of plyometric training - Turner, A. M.; Owings, M.; Schwane, J. A. (The Journal of Strength and Conditioning Research, 2003)
This study determined whether a 6-week regimen of plyometric training would improve running economy (i.e., the oxygen cost of submaximal running). Eighteen regular but not highly trained distance runners (age = 29 ± 7 [mean ± SD] years) were randomly assigned to experimental and control groups. All subjects continued regular running training for 6 weeks; experimental subjects also did plyometric training. Dependent variables measured before and after the 6-week period were economy of running on a level treadmill at 3 velocities (women: 2.23, 2.68, and 3.13 m·s-1; men: 2.68, 3.13, and 3.58 m·s-1), O2max, and indirect indicators of ability of muscles of lower limbs to store and return elastic energy. The last were measurements during jumping tests on an inclined (20°) sled: maximal jump height with and without countermovement and efficiencies of series of 40 submaximal countermovement and static jumps. The plyometric training improved economy (p < 0.05). Averaged values (m/ml·kg) for the 3 running speeds were: (a) experimental subjects-5.14 ± 0.39 pretraining, 5.26 ± 0.39 posttraining; and (b) control subjects-5.10 ± 0.36 pretraining, 5.06 ± 0.36 posttraining. The O2max did not change with training. Plyometric training did not result in changes in jump height or efficiency variables that would have indicated improved ability to store and return elastic energy. We conclude that 6 weeks of plyometric training improves running economy in regular but not highly trained distance runners; the mechanism must still be determined.